2015
DOI: 10.1177/0003319715611826
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Drug-Eluting Balloons for Patients With In-Stent Restenosis

Abstract: The optimal treatment for in-stent restenosis (ISR) of both bare-metal stent (BMS) and drug-eluting stent (DES) is currently unclear. The aim of this meta-analysis was to assess the role of drug-eluting balloon (DEB) as an optional treatment for ISR. We searched PubMed, MEDLINE, EMBASE, BIOS, and Web of Science from 2005 to July 2014. Eight studies, enrolling 1413 patients were included. Main end points were late lumen loss (LLL), binary in-segment restenosis (BR), major adverse cardiac events (MACEs), target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A meta-analysis of trials using PEB for the treatment of BMS or DES ISR showed a significant reduction in the risk of occurrence of MACE (P<0.001), TLR (P=0.006), and the recurrence of binary in-segment restenosis (P<0.001) in the group with PEB compared with an inhomogeneous control group (POBA, PES). 22 Similarly, Gao et al 23 found that the treatment of ISR with PEB significantly reduced MACE (P<0.01), death (P=0.04), TLR (P<0.01), and LLL (P<0.01) compared with POBA; however, the differences were not significant when compared with DES (PES/EES).…”
Section: Resultsmentioning
confidence: 91%
“…A meta-analysis of trials using PEB for the treatment of BMS or DES ISR showed a significant reduction in the risk of occurrence of MACE (P<0.001), TLR (P=0.006), and the recurrence of binary in-segment restenosis (P<0.001) in the group with PEB compared with an inhomogeneous control group (POBA, PES). 22 Similarly, Gao et al 23 found that the treatment of ISR with PEB significantly reduced MACE (P<0.01), death (P=0.04), TLR (P<0.01), and LLL (P<0.01) compared with POBA; however, the differences were not significant when compared with DES (PES/EES).…”
Section: Resultsmentioning
confidence: 91%
“…CHD is the most common cardiovascular disease, primarily due to coronary artery stenosis or obstruction caused by atherosclerosis [22] . PCI is one of the important tools for the treatment of CHD, but the consequent occurrence of restenosis severely affects the efficacy of PCI in CHD patients [23–25] . Although drug-eluting stents can reduce the incidence of restenosis in the short term, the incidence of restenosis remains high in the end.…”
Section: Discussionmentioning
confidence: 99%
“…Stent thrombosis after the treatment of ISR with DCB angioplasty is rare. 8) Although the doctor insisted that the patient take oral aspirin and clopidogrel after DCB treatment, she suffered from STEMI due to late stent stenosis. Further examinations indicated the patient might have antiplatelet resistance due to gene mutations.…”
Section: Discussionmentioning
confidence: 99%